MULTEM2: A new version of the program for transmission and band-structure calculations of photonic crystals - N. Stefanou; V. Yannopapas; A. Modinos (Computer Physics Communications, 2000)
We present a new version of a program for the calculation of the frequency band structure of an infinite photonic crystal, and of the transmission, reflection and absorption coefficients of light by a slab of this crystal. The crystal consists of a stack of identical slices parallel to a given surface; a slice may consist of a number of different components, each of which can be either a homogeneous plate or a multilayer of non-overlapping spherical particles of given periodicity parallel to the surface. The homogeneous media to the left and right of the slab may be different (have different real and positive dielectric functions and magnetic permeabilities).